2003
DOI: 10.1016/s0006-3495(03)74658-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Tension Spectroscopy and Strength of Biomembranes

Abstract: Rupturing fluid membrane vesicles with a steady ramp of micropipette suction produces a distribution of breakage tensions governed by the kinetic process of membrane failure. When plotted as a function of log(tension loading rate), the locations of distribution peaks define a dynamic tension spectrum with distinct regimes that reflect passage of prominent energy barriers along the kinetic pathway. Using tests on five types of giant phosphatidylcholine lipid vesicles over loading rates(tension/time) from 0.01-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

57
496
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(555 citation statements)
references
References 27 publications
57
496
2
Order By: Relevance
“…2 is applicable to estimate the contact area, which leads to a compressive stress ranging from 17 to 43 kPa. This also is in reasonable agreement with our results, especially taking into account that incorporating peptides into lipid bilayers (hence getting a model somewhat closer to a cell membrane) makes them easier to break, according to micropipette aspiration (44) and AFM indentation (42) measurements. Kagiwada et al (45) reported that a typical force of 3 nN is required to insert a nanoneedle of 200 nm in diameter into a cell.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2 is applicable to estimate the contact area, which leads to a compressive stress ranging from 17 to 43 kPa. This also is in reasonable agreement with our results, especially taking into account that incorporating peptides into lipid bilayers (hence getting a model somewhat closer to a cell membrane) makes them easier to break, according to micropipette aspiration (44) and AFM indentation (42) measurements. Kagiwada et al (45) reported that a typical force of 3 nN is required to insert a nanoneedle of 200 nm in diameter into a cell.…”
Section: Discussionsupporting
confidence: 91%
“…In another study using nanoneedle geometries, Xie et al (46,47) investigated the penetration of nanowires fixed to a substrate into cells that adhere to this substrate. They used a cell membrane rupture criterion based on activation energy theory and leading to a critical membrane tension to be reached before rupture (42,44). In the study of Xie et al, tensile forces of~1 nN are applied to the tips of nanowires of radius R ¼ 50 nm.…”
Section: Discussionmentioning
confidence: 99%
“…What is perhaps more interesting is the observation that a significant (i.e., a 10-fold) decrease of L fluct relative to L fluct;free is obtained only when ðs' 2 =4p 2 k 0 ÞT1 or ða 2 ' 4 =ð16p 4 k 0 ÞÞT1. In the former case, sTðð4p 2 k 0 Þ=' 2 Þ $ 20 k B T= nm 2 , a value comparable to reported values of the membrane rupture tension (28). In the latter case, a 2 Tðð16p 4 k 0 Þ=' 4 Þ, or, upon introducing the root mean-square (RMS) height fluctuation, w 2 hhh 2 i 0 ¼ ðpk B T=ða 2 ' 2 ÞÞ, the condition becomes ðw='Þ(½k B T=16p 3 k 0 1=2 $ 10 À2 , where we have employed k 0 z20 k B T, appropriate for the Ld phase (21).…”
Section: Case Ii: Partially Co-localized Domainssupporting
confidence: 84%
“…Unfunctionalized probes were first measured to determine E 0 and γ for the situation where penetration of the underlying bilayer is the rate-limiting step, rather than bilayer adhesion to the band. The energy barrier height of 13.0±1.6k b T for the unfunctionalized case is in excellent agreement with the previously reported 16 energy barrier for defect formation and failure in SOPC bilayers of ~13.6k b T.…”
supporting
confidence: 91%